3D-to-2D phase transformation through highly ordered 1D crystals from transition-metal oxides to dichalcogenides. (July 2021) - Lee, Hyangsook; Cho, Yeonchoo; Jeong, Kwang-Sik; Park, Taejin; Leem, Mirine; Ahn, Wonsik; Kim, Hoijoon; Kim, Jung-Hwa; Kim, Heegu; Cho, Mann-Ho; Lee, Eunha; Kim, Hyoungsub; et al.
Graphical abstract: Abstract: Although solid-state phase transformations through chemical reaction with the surrounding environment are important in the field of materials science, the atomic-level dynamics at reacting surfaces have been difficult to observe directly. Herein, we found highly ordered arrays of 1D intermediate crystals with a unique atomic configuration during the thermal sulfidation of 3D-structured MoO2 to 2D layer-structured MoS2 . These arrays reveal a dimension-breaking reconstruction process (3D → 1D → 2D) as well as a unique electronic structure evolution. Theoretical calculations show that the 1D crystals have a cross-sectional structure of four transition-metal atoms arranged in a diamond shape; these are critical to the atomic layer-by-layer formation of 2D transition-metal dichalcogenides. Furthermore, electronic structure analyses reveal that the 1D intermediate crystals alter the MoO2 /MoS2 contact structure from p- to n-type with increases in the number of formed MoS2 layers.